Criminosos, crianças e selvagens. A maldade humana, na cultura portuguesa, no ocaso do século XIX - Ana Maria Pina (Ler História, 2007)
This article analyses the perspectives on crime and the criminal of three Portuguese intellectuals of the end of the 19th Century: Basílio Freire, Afonso Costa and Ferreira Deusdado. Only Basílio, physician, defends criminal anthropology and its vision of the criminal. Afonso Costa, lawyer, as well as Deusdado, educationalist, refuse it. While for Deusdado, the criminal is someone who chooses the wrong way, for Costa, the criminal is the product of an unfair society. Only the socialism, with the abolition of the property, can solve the problem of the crime. Such differences of opinion are not explained by the partisan options. Basílio and Costa are republican, Deusdado is monarchist. The question lays in the fact that Medicine is deeply penetrated by the doctrines of criminal anthropology, while Law and Pedagogy are areas that maintain ideas with enlightment era roots.